Business Strategy, Human Resource Management Practices and Employee Outcomes: Structural Equation Modeling - Koon, Vui Yee (2012)
This study investigated the effects between two business strategies (differentiation and low-cost) and six human resource management (HRM) practices (recruitment & selection, training & development, compensation, performance management, employment security and work-life balance) on employee outcomes (organisational commitment, employee turnover, employee involvement and job satisfaction) and the extent to which such effects bring differences to Public and Private Limited companies in Malaysia. Therefore, the main objective of this study was to develop the conceptual model to measure the interaction effects of business strategy, HRM practices on employee outcomes. Four sub-objectives investigated to accomplish the main objective of the study. The first sub-objective was to investigate the effect of different business strategy to HRM practices. The second sub-objective of this study was to investigate the effect of business strategy and HRM practices on the four variables of employee outcomes. The third sub- objective of this study was to investigate whether any variance or differences among Public and Private Limited companies of the effect between business strategy and HRM practices. The fourth sub-objective was to investigate whether any variance among Public and Private Limited companies of the interrelationship between business strategy and HRM practices on employee outcomes. Structural equation modelling was used to examine the effect of business strategy to HRM practices and the interrelationships of them to employee outcomes The psychometric properties of these measures were investigated through confirmatory factor analysis. This study found that differentiation strategy was one of the business strategies that tend to emphasize on all six HRM practices while low-cost strategy found to emphasize on four HRM practices only. HRM practices found to mediate the interaction of business strategy and employee outcomes. The results also indicated that the effects of business strategy and HRM practices implemented in Public Limited companies on employee outcomes were only slightly different from the ones implemented in Private Limited companies. Types of business ownership moderate the interrelationship effect of business strategy and HRM practices on employee outcomes. The results showed invariant between differentiation strategy but variant in tow-cost strategy.